Non-formal learning strategies for regional development a pilot project - Baylon, Angelita C.
This study defined the community environment where learning occurs and attempted to a.) determine what the administrative component in the area of study is doing; b.) find out what the teachers are doing in the different subjects in relation to the nonformal aspects; c.) look into the supporting activities provided by the school; and d.) determine what is the response of the community as teaching strategies in relation to what the school does. The study is limited in scope to the two municipalities in Region XI in Mindanao, namely, Digos in Davao del Sur and Koronadal in South Cotabato. Perceptions of the people towards programs and activities were determined through verbal commitments, attitudinal and behavioral responses.